Pengaruh Digital Banking terhadap Pengguna Layanan Digital Bank Syariah pada Mahasiswa Fakultas Ekonomi dan Bisnis di Purwokerto - Ubaidillah; Anggih Dea Pratiwi (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2023)
The rapid development of technology can create fundamental changes in human life. This technological development provides benefits for human life and offers various conveniences in various aspects, including the world of banking. This technological development can certainly be an opportunity in the banking world to take advantage of technological developments to provide services to customers. The use of technology in the banking world is usually referred to as Digital Banking which includes Automatic Teller Machines, Mobile Banking, and Internet Banking. With the existence of digital banking, it is hoped that banks can provide more innovative and efficient services so that customers who use them will have their hopes and goals fulfilled in transactions, so that later they will be loyal or loyal in using this banking service. The purpose of this study is to determine whether Digital Banking services consisting of Authomatic Teller Machine (ATM), Mobile Banking, and Internet Banking affect the loyalty of users of Islamic bank digital services. Furthermore, this study used a quantitative approach. By sampling with purposive sampling technique. The source of the data used is primary data obtained from the results of filling out questionnaires. While the analysis tool used is SPSS 25 using multiple linear regression analysis methods. Based on the results of research and data processing that has been done by researchers, then the results show that the Automatic Teller Machine (ATM) has a significant effect on the loyalty of users of Islamic bank digital services, Mobile Banking has a significant effect on the loyalty of users of Islamic bank digital services, Internet Banking has a significant effect on loyalty of users of Islamic bank digital services.